Analisis Mekanisme 3R pada Penyelesaian Pembiayaan Murabahah Bermasalah di KSPPS Al-Ishlah Mitra Sejahtera Cabang Dukupuntang: Rescheduling, Reconditioning, Restructuring - Rifqoh, Zana Vania; Ulfah, Mariyah; Saefullah, Eef (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2024)
This study aims to analyze the rescheduling, reconditioning, and restructuring mechanisms used by KSPPS Al-Ishlah Mitra Sejahtera Dukupuntang branch in an effort to resolve problematic murabahah financing. This research design uses a case study, namely a case study at KSPPS Al-Ishlah Mitra Sejahtera Dukupuntang branch. This type of research is field research using a qualitative descriptive approach. Based on the findings of this study, it shows that the implementation of financing restructuring (rescheduling, reconditioning, restructuring) is only carried out for members who experience a decrease in income or a decrease in business conditions and still have good intentions. The mechanism of rescheduling, reconditioning, and restructuring at KSPPS Al-Ishlah Mitra Sejahtera Dukupuntang branch is almost the same, which is carried out on submissions from members, it's just that there are differences at certain points, more precisely in the allocation and conditions of members. The three policies are carried out by extending the installment schedule, without adding to the remaining obligations. With this research, it can contribute in the form of information or contribution of thoughts to readers or students in order to develop economic science. This research is really the author's own work, and has never been researched by anyone before, especially at KSPPS Al-Ishlah Mitra Sejahtera Dukupuntang branch, and this is something new in this study.